Building community-driven vertical greening systems for people living on less than £1 a day: A case study in Nigeria. (March 2018) - Akinwolemiwa, Oluwafeyikemi H.; Bleil de Souza, Clarice; De Luca, Luigi M.; Gwilliam, Julie
Abstract: This paper reports and evaluates the process involved in designing and building affordable community-driven vertical greening systems (VGS) prototypes in a low-income neighbourhood of Lagos, Nigeria. Prototypes are intended to fulfil the dual function of improving indoor thermal comfort conditions and providing substrate to grow edible and medicinal plants. Besides that, the research aims to identify entrepreneurial competences and relationships in the community to transform the prototypes into commercially viable local products. 'Qualitative fieldwork' is used as a methodological approach and a product development roadmap is proposed that reports: design and construction development; performance evaluation of thermal impact and plant growth; costing; and community acceptability of the four different prototypes built in two different phases: rainy season 2014 and dry season 2016. The prototypes reduced internal air temperatures by an average of 2.3 °C, moving internal comfort conditions to the comfort zone for around 90%–100% of the time. Besides that, they provided around 16 crops of edible and medicinal plants per year. For two variants of prototypes (bamboo and prefabricated timber), the study reports a range of revenues from the sales of crops, and the estimated payback period (PBP) and internal rate of return (IRR) of the investment. Highlights: VGS prototype reduced internal air temperature by an average of 2.3 °C. The indoor comfort occupant satisfaction rate after the VGS is between 90% and 100%. VGS provided a maximum of 16 crops of food and medicinal plants per year. The low income community opinion about the VGS was 100% positive. Costs are lower compared to traditional VGS but still expensive for the community.